The influence of L1 script directionality and L2 proficiency on Hanzi learning among Arabic and English learners of L2 Chinese - Zhang, Haiwei; Leah Roberts (International Review of Applied Linguistics in Language Teaching, 2022)
The present research investigates the role of L1 script directionality and L2 proficiency on the learning of Hanzi (Chinese characters) by pre-intermediate and intermediate adult Arabic (right to left) and English (left to right) learners of L2 Chinese who studied at their home country. The tasks included reading Hanzi for pronunciation, writing Hanzi according to Pinyin and meaning, and naming pseudo-Hanzi to examine phonetic radical application skills. The results showed that (1) L1 script directionality background only predicted the performance in Hanzi writing, (2) L2 proficiency was a significant predictor in Hanzi reading and Hanzi writing, and (3) L2 proficiency interacted with L1 script directionality background in phonetic radical application skills. These findings suggest that L1 script directionality background and L2 proficiency play different roles in the development of Hanzi literacy skills and orthographic awareness. The theoretical implications for the influence of L1 writing system on L2 learning and the threshold level for the development of orthographic awareness in Hanzi, and the practical implications for Hanzi instruction are discussed.